2005
DOI: 10.2206/kyushujm.59.421
|View full text |Cite
|
Sign up to set email alerts
|

CONSTRUCTION D'UN ÉLÉMENT REMARQUABLE DE L'IDÉAL DE BERNSTEIN-SATO ASSOCIÉ À DEUX COURBES PLANES ANALYTIQUES

Abstract: Etant données des déformations f1, f2 de deux polynômes de deux variables quasi-homogènes pour deux systèmes de poids distincts α1, α2 satisfaisant à des conditions similaires à celles de singularités semi-quasi-homogènes pour un poids, nous donnons, par des méthodes inspirées de celles de H. Maynadier, une formule explicite d'un polynôme de Bernstein-Sato faisant intervenir deux formes affines ρα i (f12 ), bc − ad > 0, nous calculons l'espace H f étudié récemment par J. Briançon, Ph. Maisonobe et M. Merle et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This enables an induction on i 1 and i 2 , so that we can go back to ξ 0,0 = f s 1 1 f s 2 2 . Now let us see how the proof of [3] can be adapted to prove our claim.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…This enables an induction on i 1 and i 2 , so that we can go back to ξ 0,0 = f s 1 1 f s 2 2 . Now let us see how the proof of [3] can be adapted to prove our claim.…”
Section: Resultsmentioning
confidence: 96%
“…• x i and some k ∈ N. Proof of the claim. The proof follows [3]. Let us first review it and then explain how it can be adapted to our situation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This example has been stimulating several authors for several years (in the global case and in the local case see e.g. Bahloul [Bah01,Bah05b], Castro-Jiménez and Ucha-Enríquez [CJ-UE04, §3.4] and Gago-Vargas et al…”
Section: Examplementioning
confidence: 98%
“…See also Bahloul (2005a) for a constructive proof. Theoretical studies on Bernstein-Sato ideals can also be found in, e.g., Maynadier (1997), Briançon and Maynadier (1999), Briançon and Maisonnobe (2002), and Bahloul (2005b).…”
Section: ∂ X N the Ring Of Differential Operators With Coefficienmentioning
confidence: 99%